Antimicrobial Susceptibility in Escherichia coli isolates from Guinea Fowls (Coturnix coturnix japonica) and Quails (Numida meleagris) in Ibadan, Oyo-State, Nigeria (2021)
Poultry are reared for meat, eggs and feathers. Poultry production is classified into four sectors which are chickens, ducks, guinea fowl, turkey and geese based on the marketing of poultry products and the level of biosecurity. Intensive poultry farming falls under chickens, ducks, guinea fowl and turkey characterized by moderate to high levels of biosecurity, while geese pertain to the ‘backyard’, ‘village’ or ‘family’ poultry system, with few or no biosecurity measures. Avian colibacillosis is an infectious disease of birds caused by Escherichia coli which is considered as one of the principal causes of morbidity and mortality, associated with heavy economic losses to the poultry industry by its association with various disease conditions, either as primary pathogen or as a secondary pathogen. This study determined the prevalence and antibiotic susceptibility of Escherichia coli from guinea-fowl (Numida meleagris) and quail (Coturnix coturnix japonica) in Ibadan. A total of 180 cloacal sample was collected and bacteriologically analysed for the presence of Escherichia coli. For bacteriological analysis samples were pre-enriched in peptone broth and incubated overnight at 370C, followed by a selective isolation on MacConkey agar supplemented with ampicillin (lOOmg/L). Ampicillin-rcsistant isolates were subcultured on MacConkey agar supplemented with cefotaxime (lmg/L). Biochemical tests of all the cefotaxime resistant isolates was performed. Double disc diffusion test specific for Extended Spectrum Beta Lactamase producing E. coli (ESBL E.coli) was performed. Antibiotic sensitivity testing was done using Mueller-Hinton agar. Twenty -six isolates were analysed using disc diffusion method. Eighty - Four (84) isolates were lactose fermenters, 49 isolates were Ampicillin-rcsistant E. coli and 26 isolates were Cefotaxime-resistant E. coli and none was positive for ESBL-E. coli. Gentamycin has the highest sensitivity of 100% followed by ciprofloxacin of 96.2% of E. coli isolates while amoxicillin-clavulanic (96.2%). tetracycline (96.2%) and sulphamethaxazole (92.3%) has the highest rate of resistance. This present study investigated antimicrobial susceptibility of Escherichia coli isolated from guinea fowls and quail in Ibadan, Nigeria.